Overview Challenges Affecting the Promotion of Good Corporate Governance Measures in Mahikeng Local Municipality: Array - Chitimira, Howard; Sethunyane, Tumelo; Magau, Phemelo (Acta Universitatis Danubius. Juridica, 2021)
The adoption of poor corporate governance measures has to date given rise to many problems of corruption, embezzlement of public funds and maladministration in several municipalities in South Africa, including the Mahikeng local municipality. The Mahikeng local municipality has had a bad reputation of corruption, embezzlement of public funds and maladministration challenges in the recent years. These challenges are reportedly perpetrated by the municipal manager who is responsible for the management of the municipal budget and related funds. Moreover, irregular expenditure, wasteful and irregular expenditure, non-compliance with the relevant laws, poor management, political interference, lack of political will and lack of accountability are further challenges that have crippled the proper and effective management of the Mahikeng local municipality. In light of this, this article investigates the adequacy and enforcement of the relevant laws to promote good corporate governance in Mahikeng local municipality. This is done to recommend the adoption and utilisation of good corporate governance principles and related measures to, inter alia, promote accountability and consequent management of the Mahikeng local municipality.